Thrombolysis for Acute Ischemic Stroke Following Transcatheter Aortic Valve Replacement: Case Report and Literature Review. Issue 2 (March 2020) - Malhotra, Ashwin; Segal, Alan Z.
Abstract : Introduction: Intravenous thrombolytic therapy with recombinant tissue type plasminogen activator (IV-tPA) is the first-line treatment option for acute ischemic stroke (AIS). The tPA exclusion criteria, defined decades ago, require updates as new technologies emerge. Transcatheter aortic valve replacement (TAVR), which has begun to replace open surgery, poses a risk for acute stroke and falls outside of prior tPA guidelines. Case Report: Here we describe a post-TAVR patient treated safely with IV-tPA for presumed AIS. Conclusion: Previously undescribed, we suggest that tPA should be considered for post-TAVR AIS patients who otherwise satisfy inclusion and exclusion criteria.